Analisis Hubungan dan Implikasi Nilai-Nilai Karakter Dalam Kompetensi Inti - Hakim, Ilham Faiqul; Naili, Maftuhah; Sabrina, Adinda; Anja, Isna; Iqbal, Muhammad (STAI Asy-Syukriyyah, 2024)
This study aims to analyze the relationship and implications of character values in core competencies (IC), basic competencies (KD), learning outcomes (CP), indicators of competency achievement (GPA), and learning objectives in the context of Islamic religious education. The literature research method for the theme